Memorial in Welsh coal, slate and steel for the Welshmen who lost their lives in support of the Spanish Republic. South Wales Miners' Library, University College Swansea (1976)
Memorial in Welsh coal, slate and steel for the Welshmen who lost their lives in support of the Spanish Republic. South Wales Miners' Library, University College Swansea.